Cryptography and the Global South: secrecy, signals and information imperialism. Issue 11 (31st July 2020) - Dover, Robert; Aldrich, Richard J.
Abstract: For decades, espionage during the Cold War was often presented as a competition between East and West. The extent to which the Global South constituted the main battleground for this conflict is now being appreciated, together with the way coups and covert regime change represented a continuation of colonialism by other means. Recent revelations about the nature of technical surveillance and signals intelligence during this period paint an even more alarming picture. New research materials released in Germany show the ways in which Washington, London and even Moscow conspired to systematically attack the secure communications of the Global South. For almost half a century, less advanced countries were persuaded to invest significant sums in encryption machines that were adapted to perform poorly. This was a deceptive system of non-secrecy that opened the sensitive communications of the Global South to an elite group of nations, that included former colonial rulers, and emergent neo-imperial powers. Moreover, the nature of this technical espionage, which involved commercial communications providers, is an early and instructive example of digital global information inequality.